The mating of a fly. - Hall, J.C. (Science, 1994)
Courtship in Drosophila is influenced by a wide variety of genes, in that many different kinds of pleiotropic mutations lead to defective courtship. This may seem to be a truism, but the broad temporal and spatial expression of most of the fly's "neuro genes" makes it difficult to exclude elements of such genes' actions as materially underlying reproductive behavior. "Courtship genes" that seem to play more particular roles were originally identified as sensory, learning, or rhythm mutations; their reproductive abnormalities have been especially informative for revealing components of male or female actions that might otherwise have gone unnoticed. Further behavioral mutations seemed originally to be courtship-specific, turned out not to have that property, and have led to a broadened perspective on the nature and action of Drosophila's sex-determination genes.